2001
DOI: 10.1073/pnas.061002998
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Alzheimer's disease have reduced activities in midlife compared with healthy control-group members

Abstract: The development of Alzheimer's disease (AD) later in life may be reflective of environmental factors operating over the course of a lifetime. Educational and occupational attainments have been found to be protective against the development of the disease but participation in activities has received little attention. In a casecontrol study, we collected questionnaire data about 26 nonoccupational activities from ages 20 to 60. Participants included 193 people with probable or possible AD and 358 healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
279
1
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 376 publications
(294 citation statements)
references
References 43 publications
9
279
1
5
Order By: Relevance
“…Such a difference was not observed during the second stage when COV and ALZV animals showed a similarity in maze performance. This is consistent with some previous retrospective [24,25] and prospective longitudinal [23,26] studies that support the hypothesis that in- creased use of cognitive skills and higher levels of education can protect against the development of AD. However, epidemiological studies cannot determine which activities or the combination of them are more important [27] .…”
Section: Discussionsupporting
confidence: 92%
“…Such a difference was not observed during the second stage when COV and ALZV animals showed a similarity in maze performance. This is consistent with some previous retrospective [24,25] and prospective longitudinal [23,26] studies that support the hypothesis that in- creased use of cognitive skills and higher levels of education can protect against the development of AD. However, epidemiological studies cannot determine which activities or the combination of them are more important [27] .…”
Section: Discussionsupporting
confidence: 92%
“…Others have reported that patients with AD were less active during their adulthood than subjects without dementia. [40][41][42][43][44][45] These case-control studies are even more prone to methodological bias.…”
Section: Physical Activity and The Prevention Of Dementia Ad Or Cogmentioning
confidence: 99%
“…A retrospective case control study reported that patients with AD were less active (both intellectually and physically) in midlife and that inactivity was associated with a 250% increased risk of developing AD [7] . Similarly, a prospective study also demonstrated that physical activity was protective against the development of cognitive impairment, AD, and any types of dementia, and that the highest activity group showed a 60% decrease in the incidence of AD [8] .…”
Section: Exercise Decreases Risks Of Alzheimer's Disease (Ad)mentioning
confidence: 99%